Eurycoma Longifolia Upregulates Osteoprotegerin Gene Expression In Androgen-deficient Osteoporosis Rat Model - Nadia Mohd Effendy; Ahmad Nazrun Shuid; Eman El-arab; Halimaton Saadiah Abdul Razak; Norliza Muhammad; Norazlina Mohamed; Ima Nirwana Soelaiman (BioMed Central Ltd., 2024)
Indexed by Scopus